2015
DOI: 10.5664/jcsm.5186
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Characteristics of Children with Central Disorders of Hypersomnolence Versus Matched Healthy Children

Abstract: Background: Hypersomnia of central origin from narcolepsy or idiopathic hypersomnia (IHS) is characterized by pathological levels of excessive daytime sleepiness (EDS). Central hypersomnia has historically been underdiagnosed and poorly understood, especially with respect to its impact on daytime functioning and quality of life in children. Objective: Describe the psychosocial adjustment of children treated for narcolepsy or IHS on school performance, quality of life, and physical/extracurricular activities. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Quality of life and daytime functioning can be profoundly affected in patients with IH, even following treatment (5052). Although the distinction between IH with mood dysfunction and hypersomnia associated with a psychiatric disorder can be challenging (41), symptoms of depression are commonly encountered in people with IH and may add to the burden of disease (52).…”
Section: Non-pharmacologic Treatment Optionsmentioning
confidence: 99%
“…Quality of life and daytime functioning can be profoundly affected in patients with IH, even following treatment (5052). Although the distinction between IH with mood dysfunction and hypersomnia associated with a psychiatric disorder can be challenging (41), symptoms of depression are commonly encountered in people with IH and may add to the burden of disease (52).…”
Section: Non-pharmacologic Treatment Optionsmentioning
confidence: 99%
“…The Avis et al 28 study included children with a variety of central disorders of hypersomnolence: narcolepsy with cataplexy (n = 7), narcolepsy without cataplexy (n = 11), idiopathic hypersomnia (n = 15), and 33 healthy controls. It found that all children with a central disorder of hypersomnolence scored significantly lower on academic grades with a Cohen effect size value suggesting a moderate practical significance.…”
Section: Academic Achievement and Hypersomnolencementioning
confidence: 99%
“…The interviews yielded descriptions of the impact such as: "deterioration in school performance", or "decrease in academic performance", or "school functioning is identified as significantly lower" following the onset of narcolepsy. Because only one study had included a population of children with idiopathic hypersomnolence (n = 15), no generalisations can be drawn for that population, however, this study did identify that all children with central hypersomnia had lower academic grades, and were significantly sleepier than healthy Chapter Four: Published Literature Review -Associations between neuropsychological, neurobehavioural and emotional functioning and either narcolepsy or idiopathic hypersomnia in children and adolescents 78 children (Avis, Shen, et al, 2015). The proportion of children and adolescents with narcolepsy who had repeated a year was also significantly higher than that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The Avis, Shen, et al (2015) study included children with a variety of central disorders of hypersomnolence: narcolepsy with cataplexy (n = 7), narcolepsy without cataplexy (n = 11), idiopathic hypersomnia (n = 15), and 33 healthy controls. It found that all children with a central disorder of hypersomnolence scored significantly lower on academic grades with a Cohen's effect size value suggesting a moderate practical significance.…”
Section: Academic Achievement and Hypersomnolencementioning
confidence: 99%
See 1 more Smart Citation